A Proposed Model of Ict Competence Among Lecturers in The Central Zone Vocational Colleges, Malaysia - Thamarai Thamodharan; Muhammad Faizal A. Ghani (EARR (Educational Administration Research and Review), 2022)
The use of information technology has become an important that has changed the learning process and implementation of educational organizations. (Syamsul A. Hamid, 2021). Several studies show that the use of information technology in organizations increases employee productivity and job performance. at the same time, Previous studies (Raman, Thannimalai, Ismail, 2019) found that the level of lecturer competence among vocational college lecturers is moderate. Therefore, it is desirable to conduct up -to -date research. Objectives of this study was to identify the level of ICT competence of lecturers in Central Zone Vocational College, Malaysia. Descriptive analysis was conducted with regards to mean and standard deviation. Second objective was to test the relationship between the dimension and subdimension of standard competency model, and the effectiveness of ICT in the Central Zone Vocational College, Malaysia. Inferential analysis was used to identify contribution of exogenous variable to endogenous variable through Structural Equation Modeling (SEM) using AMOS. This study uses a quantitative approach through survey method. Questionnaires were distributed to 388 lecturers in central zone vocational colleges, Malaysia. They were randomly selected evenly. Data analysis was performed using the Statistical Package for the Social Science (SPSS) version 25. The findings showed that, the data of this study indicated high level of competency in ICT among lecturers in Central Zone Vocational College, Malaysia when the mean score exceeds 6.68. Furthermore, the results of the analysis showed the value of the fitness indexes of this model meets the suggested fitness index by previous researchers, namely with the normed chi-square values (χ2/df) was 2.875 ( 5.0), CFI = 0.970 ( 0.90), TLI = 0.963 ( 0.90), GFI = 0.901 ( 0.90) and RMSEA = 0.070 ( 0.08). In conclusion, data collected showed that the proposed structural model does achieve the level of fitness required. This also indicate that the proposed model of lecturer’s competency in the central zone vocational college, Malaysia are fit with the data. The implications of the study indicate that the role of lecturers as educators is important in developing appropriate reforms in supporting the innovations that take place in educational organizations. Apart from that, the findings also provide a new perspective in the implementation of innovation in the education system in Malaysia.